Innovative bean sprouts basket (iBSB): A conceptual paper on a new dimension of low-cost bean sprout cultivation among agro-community - Yusuf Munifah Siti Amira; Takrim Aiman; Lazim Siti Saripa Rabiah Mat (BIO Web of Conferences)
Sprouts are tiny seedlings that are produced during seed germination and have a short growth period. Across the globe and in Malaysia, more people are consuming bean sprouts due to their awareness of the need to consume “healthy foods”. The sprouts are composed of proteins, carbohydrates, and biochemical compounds with a significant amount of the recommended daily requirement for ascorbic acid and riboflavin, as well as a variety of minerals obtained through the consumption of sprouts. Moreover, sprout quality is influenced by the length, thickness, colour, and texture of the hypocotyl and roots, as well as by maintaining characteristics and little water loss after harvest. A modified atmosphere with high carbon dioxide and low oxygen can be used as a sprouting environment to control sprout growth. However, the current issues relating to open sprouting systems are bean sprout disease and high maintenance for open cultivation tanks. Thus, to solve the problem regarding the current domestic bean sprouting system, an innovative bean sprouts basket (iBSB) was innovated to control or reduce bean sprout disease for every production cycle.